Electrochemical vs antibacterial characterization of ZrCN-Ag coatings - Velasco, Sebastian Calderon (2015)
Nowadays, antibacterial properties are becoming a viable feature to be introduced in biomaterials due to the possibility of modifying the materials' surface used in medical devices in a micro/nano metric scale. As a result, it is mandatory to understand the mechanisms of the antimicrobial agents currently used and their possible failures. In this work, the antibacterial activity of ZrCNAg films is studied, taking into consideration the ability of silver nanoparticles to be dissolved when embedded into a ceramic matrix. The study focuses on the silver release evaluated by glow discharge optical emission spectroscopy and the effect of the fluid composition on this release. The results revealed a very low silver release of the films, leading to non-antibacterial activity of such materials. The silver release was found to be dependent on the electrolyte composition. NaCl (8.9 g L? 1) showed the lowest spontaneously silver ionization, while introducing the sulfates in Hanks' balanced salt solution (HBSS) such ionization is increased; finally, the proteins incorporated to the (HBSS) showed a reduction of the silver release, which also explains the low ionization in the culture medium (tryptic soy broth) that contains high quantities of proteins.